Increased Connexin36 Phosphorylation in AII Amacrine Cell Coupling of the Mouse Myopic Retina - Banerjee, Seema; Wang, Qin; Zhao, Fuxin; Tang, George; So, Chunghim; Tse, Dennis; To, Chi-Ho; Feng, Yun; Zhou, Xiangtian; Pan, Feng (Frontiers in Cellular Neuroscience, 2020)
Myopia is a substantial public health problem worldwide. In the myopic retina, distant images are focused in front of the photoreceptors. The cells and mechanisms for retinal signaling that account either for emmetropization (i.e., normal refraction) or for refractive errors have remained elusive. Gap junctions play a key component in enhancement of signal transmission in visual pathways. AII amacrine cells (ACs), coupled by Connexin 36, segregate signals into ON and OFF pathways. Coupling between AII ACs is actively modulated through phosphorylation at serine 293 via dopamine in the mouse retina. In this study, form deprivation mouse myopia models were used to evaluate the expression patterns of connexin36-positive plaques (structural assay) and the state of connexin36 phosphorylation (functional assay) in AII ACs, which was GPF-expressing in the Fam81a mouse line. Single cell RNA sequencing showed dopaminergic synapse and gap junction pathways of AII amacrine cells were downregulated in the myopic retina, although Gjd2 mRNA expression remained the same. Compared with the normal refractive eye, phosphorylation of connexin36 was increased in the myopic retina, but expression of connexin36 remained unchanged. This increased phosphorylation of Cx36 could indicate increased functional gap junction coupling of AII amacrine cells in the myopic retina, a possible adaptation to adjust to the altered noisy signaling status.